PENGARUH PERSEPSI DAN PENGALAMAN TERHADAP KEPUTUSAN MEMILIH UNIVERSITAS MUHAMMADIYAH PALEMBANG - Puspasari, Mardiana; Nurrahmi, Maftuhah; Handhiko, Bagoes; Fitriah, Wani (Universitas Muhammadiyah Palembang, 2021)
These objectives of this study were to find out whether or not there were any significant effects of perception and experience on the decision making to choose Muhammadiyah University of Palembang. The type of this study was an associative, with the variables used were perception, experience and decision making. The sample chosen were 100 respondents, with the data collection method using a questionnaire. The analysis technique in this study used multiple linear regression analysis. The results of simultaneous hypothesis testing showed the value of Fcount > Ftable, which meant that there was a significant effect of perception and experience on the decision making to choose Muhammadiyah University of Palembang. The results of the partial hypothesis test showed the value of tcount > tcount, which meant there was a significant effect of perception on the decision making to choose Muhammadiyah University of Palembang, and there was a significant effect of experience on the decision making to choose Muhammadiyah University of Palembang. The value of the coefficient of determination showed that the variables of perception and experience were able to contribute to the ups and downs of the decision making to choose Muhammadiyah University of Palembang, by number 33.2%.